Influência da desconexão de habitats na quitridiomicose e no microbioma cutâneo de anfíbios anuros - Martins, Renato Augusto (2020)
Habitat split can be defined as the human-induced discontinuity between habitats used by different stages of the life history of a species. The main affected species are those that need to migrate between distinct habitats to complete their reproductive cycle, as most amphibians species. Much of the ongoing amphibian declines around the world, including Brazil, are based on the emergence of the waterborne chytrid fungus Batrachochytrium dendrobatidis (Bd). Although it is already known that habitat split is linked to an increased risk of local amphibian declines and extinctions, little is known how habitat split at the landscape scale increases the risk of chytridiomycosis. It is also known that the symbiotic cutaneous microbiota (the microbiome) is the first line of amphibians defenses against invasive pathogens such as Bd. Thus, disturbance in the cutaneous microbiome caused by deforestation and habitat fragmentation could reduce host defenses against Bd in highly fragmented landscapes. This study aims to test the effect of deforestation and habitat split on host-pathogen dynamics in amphibians, also investigating the relations between the amphibian microbiome diversity, composition, and habitat disturbances. Our results support the hypothesis that, the smaller the fragment and the more disconnected from permanent water bodies, the greater the Bd prevalence and infection loads in amphibian populations, regardless of amphibian reproductive strategy or migratory behavior. In addition, we found that high bacterial richness in the host skin microbiome is correlated with low Bd infections. Our findings highlight that efforts to restore natural riparian vegetation could reduce the risk of chytridiomycosis and contribute to the conservation of amphibians in the Atlantic Forest.